Papillary fibroelastoma on pulmonary valve - Valve-sparing surgery of a cardiac tumor in a rare location - Grus, Tomas; Kuchynka, Petr; Palecek, Tomas; Hadravsky, Ladislav; Urbanec, Tomas; Lambert, Lukas (Cardiovascular pathology, 2020)
We present images of a papillary fibroelastoma on a pulmonary valve - echocardiography, intraoperative images, macroscopic and microscopic images of the tumor in this uncommon location.
Keywords: Male; Cardiac Surgical Procedures; fibrom; Fibroma; mužské pohlaví; kardiochirurgické výkony; nádory srdce; lidé středního věku; plicní chlopeň; výsledek terapie; Pulmonary Valve; Treatment Outcome; Pericardium; perikard; Humans; lidé; Heart Neoplasms; Middle Aged